Attenuation of Cardiovascular Response During Laryngoscopy and Endotracheal Intubation by Using Pethidine with Lignocaine - Mollick, MT; Hossain, MD; Ali, NP (Journal of Armed Forces Medical College, Bangladesh, 2011)
A prospective comparative study was done on lignocaine versus lignocaine with pethidine to observe the effect on cardiovascular response to laryngoscopy and endotracheal intubation. One hundred such elective surgical patients of active age group (16 - 60 years) having American Society of Anaesthesiologist (ASA) physical status I & II irrespective of surgical procedure were randomly assigned to one of the two groups of 50 each. Group I received injection lignocaine 1 mg/kg intravenously 02 minutes before induction of general anaesthesia. Patients in group II received injection pethidine 1 mg/kg body weight and injection lignocaine 1 mg/kg body weight intravenously 02 minutes before induction of general anaesthesia. Haemodynamic parameter i.e. blood pressures (systolic blood pressure, diastolic blood pressure and mean blood pressure), heart rate, rate pressure product were monitored after 1st, 3rd, 5th minutes following intubation. There were statistically significant (p<0.001) increase in blood pressures, heart rate and rate pressure product in group I i.e. pretreatment with 1 mg/kg body weight intravenous lignocaine and remained so after 5 minutes. On the other hand there were no statistically significant (p>0.05) increase in heart rate, blood pressures and rate pressure product in group II, where pretreatment done with pethidine 1 mg/kg body weight with lignocaine 1 mg/kg body weight and the values returned control level before 5 minutes. The study showed that pethidine 1 mg/kg body weight with lignocaine 1 mg/kg body weight pretreatment suppresses the cardiovascular response due to laryngoscopy and intubation. Key words: Cardiovascular response; laryngoscopy; lignocaine with pethidine. DOI: 10.3329/jafmc.v6i2.7274 JAFMC Bangladesh. Vol 6, No 2 (December) 2010 pp.40-43